Rare earth La single atoms supported MoO3-x for efficient photocatalytic nitrogen fixation - Liu, Xiufan; Luo, Yani; Ling, Cancan; Shi, Yanbiao; Zhan, Guangming; Li, Hao; Gu, Huayu; Wei, Kai; Guo, Furong; Ai, Zhihui; Zhang, Lizhi (Applied catalysis. B, Environmental, 2022)
Herein, we demonstrate that the rare-earth La single catalyst with multi-shell characteristic is an excellent choice for this purpose. By merit of its unsaturated orbitals of La, the single La atom strongly bonds with the two-coordinated lattice oxygen on the oxygen-deficient MoO3−x to form O2c-La-O2c coordination. This robust metal-support interaction frees single atoms from detachment or aggregation, and prevents catalyst from deactivation. Meanwhile, the occupied 5d orbitals of La back-donate electrons to the 2π* molecular orbitals of adsorbed N2 that substantially activate the inert NN bond towards successive hydrogenation. And single La atom could optimize the electron property of the MoO3−x support to promote photocatalytic nitrogen fixation. Without any sacrificial agents, this single atom La catalyst with a well-designed coordination structure delivers an impressive NH3 production rate of 209.0 μmol h1 g 1 under visible light, outperforming most reported single atom photocatalysts. [Display omitted] •Single La atoms are successfully anchored on the MoO3−x support by bonding with two-coordinated lattice oxygen, and optimize electron structure of the support.•The coordination environment of single La atom is O2c-La-O2c structure, which act as specific active site.•Sing La atoms substantially activate the inert NN bond towards successive hydrogenation.•The ammonia yield reaches to 209.0 μmol h1 g 1 for the single La atom catalysts, nearly 10 times that of the support.